2012
DOI: 10.1007/s00221-012-3327-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cortical excitability can speed up blindsight but not improve it

Abstract: The nal publication is available at Springer via https://doi.org/10.1007/s00221-012-3327-x Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Alber et al (2017) placed the electrodes in the occipital areas (O1 or O2), depending on the brain lesion. Cowey et al (2013) stimulated the MT/V5, positioning the reference electrode in the MT/V5 contralateral area or in the right frontal pole. Matteo et al (2017) stimulated the parieto-occipital area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alber et al (2017) placed the electrodes in the occipital areas (O1 or O2), depending on the brain lesion. Cowey et al (2013) stimulated the MT/V5, positioning the reference electrode in the MT/V5 contralateral area or in the right frontal pole. Matteo et al (2017) stimulated the parieto-occipital area.…”
Section: Resultsmentioning
confidence: 99%
“… Matteo et al (2017) stimulated the parieto-occipital area. tDCS was always delivered at 2 mA intensity, except for two studies ( Cowey et al, 2013 ; Olma et al, 2013 ) that delivered it at 1.5 mA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…tDCS treatment, in fact, influenced recovery speed and entities. Studies on offline tDCS with hemianopic patients showed an improvement of motion perception in the healthy hemifield and, in one case, the increase speed of blindsight 34 , 35 ) . Although these studies documented the efficacy of tDCS in association with border rehabilitation, its effects on blindsight rehabilitation have not yet been studied.…”
Section: Introductionmentioning
confidence: 95%